Systemic glucocorticoids and the risk of breast cancer in a large nationwide case–control study - Manon Cairat; Morten Olesen; Elea Olivier; Anton Pottegård; Blánaid Hicks (Breast Cancer Research)
Abstract Background Concerns have been raised that long-term use of glucocorticoids may increase the risk of breast cancer, yet evidence is limited. Thus, this study investigated the association between systemic glucocorticoid use and breast cancer risk, overall and by breast cancer subtype and stage. Methods A nationwide case–control study was conducted using the Danish healthcare registries. Women with invasive breast cancer between 2001 and 2018 (n = 67,829) were identified as cases. Each case was matched to 10 population controls on age and calendar time. Ever users of glucocorticoids were defined as women who filled at least 2 prescriptions and long-term users those who filled prescriptions equivalent to ≥ 1000 defined daily doses (DDDs). Conditional logistic regressions were performed to calculate odds ratios (ORs) and 95% confidence intervals for the associations between glucocorticoid use and breast cancer risk. Results Twelve percent of women (n = 87,277) had ever been exposed to glucocorticoids and fewer than 1% were long-term users (n = 5,574). No association was found between ever use of glucocorticoids and breast cancer risk [OR = 1.00 (0.98—1.03)], compared with never use. However, an inverse association was observed between long-term glucocorticoid use and breast cancer risk [OR = 0.87 (0.77—0.97)], with suggestion of a slight dose–response relationship [OR per 500 DDDs = 0.96 (0.94—0.99)]. The associations were consistent across different tumour subtypes, estrogen receptor status, or clinical stage at diagnosis. Conclusion The findings from this large nationwide study did not suggest a positive association between glucocorticoids and breast cancer risk.